Patent value and survival of patents - Jung-Tae Hwang; Byung-Keun Kim; EuiSeob Jeong (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study investigated the effect of patent value on the renewal (survival) of patents. The private value of patents can be one of the main pillars sustaining a firm's value, and the estimation of the value may contribute to the strategic management of firms. The current study aimed to confirm the recent research findings with survival analysis, focusing on the more homogeneous patent data samples. In this study, a dataset is constructed from a cohort of 6646 patents from the 1996 and 1997 application years, using patent data from the European Patent Office (EPO). We found that the family size and non-patent backward citations exhibited profound impacts on patent survival. This result is in line with numerous studies, indicating the positive impact of science linkages in the biotechnology and pharmaceutical fields. It was also found that the effect of the ex-post indicator is not as strong as the ex-ante indicators, like traditional family size and backward citations. In short, the family size matters most for the survival of patents, according to the current research.
Keywords: 650; Cox hazard regression; ex-ante indicators; ex-post indicators; patent renewal; survival analysis